INTENCIÓN DE AUMENTO DE VELOCIDAD Y EVALUACIÓN DEL RIESGO SEGÚN CONTEXTOS VIALES - Moreno Salas, Marjorie; Monge López, David (Universidad de Costa Rica, 2013)
Through an exploratory study surveyed 460 drivers of cars, interested in reviewing the interaction between the handling of errors, the purpose of increasing the speed and socio-demographic variables, driving vehicles and the routes that generally are in use. The results show two scales, that because of its psychometric data, it can be used in the country to study the Psychology Psychology of the Transport.